Livestock associated epidemiological information profiling in New Sandwip Island (Jahajerchar) of the Meghna estuary, Noakhali using participatory disease searching tool - Islam, SK Shaheenur; Chakma, Shovon; Akhter, AHM Taslima; Ibrahim, Nelima; Sarker, Nurul Huda (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was conducted in New Sandwip island (Jahajerchar) of the Meghna estuary, Noakhali to explore animal species are being reared, their disease status, and also to finding out the constraints and opportunitities for keeping livestock in the island. Materials: Considering local knowledge as an epidemiological intelligence, the livestock species and their disease profile as well as livestock keeping problems were assessed through two focus group discussion with informants interview using Participatory Disease Searching (PDS) tools. The interview was conducted predominantly using semi-structured questionnaire (SSI) and other participatory epidemiology(PE) tools such as simple ranking (SR), pair-wise ranking (PWR), proportional pilling (PP) and transect work (visualization) were applied with flexibility to collect information. Results: PDS tools identified sheep (69%) is the main livestock species followed by cattle (16%) and buffalo (15%) in the island. The Peste des Petits Ruminant (PPR) in sheep (90%), anthrax in cattle (52%) and Haemorrgic Septicemia (HS) in buffalo (59%) were confirmed as top important species-wise diseases via the study. This place is prospect for sheep and buffalo raising rather than cattle. Lack of of shelter (Khella) for keeping livestock during adverse climatic condition, no access of portable water along with inadequate veterinary health care facilities were recognized as constraints for livestock raising in this island. Conclusion: This place is potential for sheep and buffalo raising rather than cattle. The study has validated the significance of accepting participatory disease searching tool in order to capture voluntarily submitted epidemiological data towards establishing a cost effective, unique national disease surveillance system in Bangladesh. http://doi.org/10.5455/javar.2017.d222